Penetapan Tarif Rasional Pelayanan Kesehatan RSUD Tenriawaru Kabupaten Bone - Darmawansyah Darmawansyah; Muhammad Yusri Abadi; Suci Rahmadani; Dian Saputra Marzuki; Ryryn Suryaman (Faculty of Public Health, Hasanuddin University, Makassar, 2018)
Tariff of health service RSUD Tenriawaru Bone Regency is still based on by law in 2012 so that needmore research about rational tariff. This study aims to obtain information on the rational tariff of several costcenter services in RSUD Tenriawaru Bone Regency. This type of observational research is intended to identifyall caracteristic used to calculate total cost (fixed cost) and total fixed operational cost (semi variable cost), andtotal operational cost is not fixed (variable cost) and tariff every action there. Sample research of all transactionsrelated to fixed costs, semi-variable costs and variable costs at cost centers. Data collection using observationaltechniques and documentation. Data analysis using unit cost analysis with microsoft excell. The result of researchshows that the health service tariff of RSUD Tenriawaru Bone Regency based on unit cost in the biggest radiologyunit is USG (Ultrasound) Rp.280.000,-; the largest physiotherapy unit is action using gymnastic pool Rp.250.000,-; hemodialysis rate on hemodialysis unit is Rp.1,000,000,-; largest NICU is resuscitation Rp.360.000,-; and unitcost of treatment classification with normative output (BOR 80%) are as follows: Main VIP Class Rp.420.000,-;VIP Class Rp.300.000,-; Class I Rp.240.000,-; Class II Rp.150.000,-; and Class III Rp.95.000,-. The conclusion ofthe calculation results in a higher rational tariff than the current service rate.